Impact of Gender on Social Media Use: A Study of Students’ Motivation to Use Facebook, Instagram, and TikTok - Dariusz ZDONEK (Communications of International Proceedings, 2021)
The paper s an attempt to identify key factors that affect social media (SM) use among students in Poland. They were investigated among respondents divided by gender. The survey involved 646 students of five Polish universities. The study shows that the most popular social media platforms among students are Facebook, YouTube, and Instagram. Statistically significant differences in SM use by women and men were found. Women are much more active on such platforms as Instagram, Snapchat, Pinterest, TikTok, Facebook, and Messenger. Meanwhile, men more often browse and comment content on YouTube, Twitter, and Discord. It has been demonstrated that the popularity of Facebook is founded mostly on the need to cater to own needs regarding studies (faster communication via Messenger, setup of independent student groups to communicate and exchange information) and habits. Other significant drivers of Facebook, Instagram, and TikTok use include entertainment, boredom, interesting information about others, and popularity among friends. Preliminary research indicated that gender has little to no effect on individual drivers of Facebook and TikTok use (no statistical differences). It was only for Instagram that women listed three drivers as much more important. These were the opportunity to share interesting information with others, the opportunity to learn interesting information about others, and the opportunity to develop one's passions.
Keywords: Social media; Key Factors; Students; Motivation; Poland.